Chemotherapy and Abdominal Wall Closure Technique Increase the Probability of Postoperative Ventral Incisional Hernia in Patients With Colon Cancer. Issue 1 (January 2023) - Santos, David A.; Zhang, Liangliang; Do, Kim-Anh; Bednarski, Brian K.; Robinson Ledet, Celia; Limmer, Angela; Gibson, Heather; You, Y. Nancy
Background: Chemotherapy is associated with postoperative ventral incisional hernia (PVIH) after right hemicolectomy (RHC) for colon cancer, and abdominal wall closure technique may affect PVIH. We sought to identify clinical predictors of PVIH. Methods: We retrospectively analyzed patients who underwent RHC for colon cancer from 2008-2018 and later developed PVIH. Time to PVIH was analyzed with Kaplan-Meier analysis, clinical predictors were identified with multivariable Cox proportional hazards modeling, and the probability of PVIH given chemotherapy and the suture technique was estimated with Bayesian analysis. Results: We identified 399 patients (209 no adjuvant chemotherapy and 190 adjuvant chemotherapy), with an overall PVIH rate of 38%. The 5-year PVIH rate was 55% for adjuvant chemotherapy, compared with 38% for none (log-rank P < .05). Adjuvant chemotherapy (hazard ratio [HR] 1.65, 95% confidence interval [CI] 1.18-2.31, P < .01), age (HR .99, 95% CI .97-1.00, P < .01), body mass index (HR 1.02, 95% CI 1.00-1.04, P < .01), and neoadjuvant chemotherapy (HR 1.92, 95% CI 1.21-3.00, P < .01) were independently associated with PVIH. Postoperative ventral incisional hernia was more common overall in patients who received adjuvant chemotherapy (46% compared with 30%, P < .01). In patients who received adjuvant chemotherapy, the probability of PVIH for incision closure with #1 running looped polydioxanone was 42%, compared with 59% for incision closure with #0 single interrupted polyglactin 910. Discussion: Exposure to chemotherapy increases the probability of PVIH after RHC, and non–short stitch incision closure further increases this probability, more so than age or body mass index. The suture technique deserves further study as a modifiable factor in this high-risk population.